1961
DOI: 10.1121/1.1908679
|View full text |Cite
|
Sign up to set email alerts
|

Wall Pressure Correlations in Turbulent Airflow

Abstract: The correlation properties of turbulent wall pressure fluctuations are investigated experimentally with a view toward developing an adequate phenomenological model of the pressure correlation function for use in engineering calculations. It was found that both mean eddy sizes and mean eddy lifetimes determined by averaging over broad frequency bands did not contain sufficient information to accurately describe the high frequency end of the turbulent power spectrum. Thus, such gross quantities are of somewhat l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1962
1962
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Details of the equipment and techniques were described in a previous work. 10 Parasitic acoustic noise in the wind tunnel presents difficulties in these measurements, since it has correlation maximums for zero time delay in lateral correlation measurements and very nearly zero time delay in longitudinal correlation measurements. The amount of acoustic noise was negligible at the highest frequencies for which measurements of L x and L y were obtained but was appreciable at the lowest frequencies and highest flow speeds.…”
Section: Wall Pressure Correlationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the equipment and techniques were described in a previous work. 10 Parasitic acoustic noise in the wind tunnel presents difficulties in these measurements, since it has correlation maximums for zero time delay in lateral correlation measurements and very nearly zero time delay in longitudinal correlation measurements. The amount of acoustic noise was negligible at the highest frequencies for which measurements of L x and L y were obtained but was appreciable at the lowest frequencies and highest flow speeds.…”
Section: Wall Pressure Correlationsmentioning
confidence: 99%
“…In previous work, 10 where £ = x ~ x\ rj = y -y', T = t -t\ (p 2 ) is the mean square pressure, v is the mean eddy drift velocity, f is the mean eddy lifetime, and L x and L v are the longitudinal and lateral eddy sizes, respectively. Actually, in the work referred to above we treat in detail only the one-dimensional form of this spectrum, but pressure correlation measurements indicate that the pressure correlation falls off exponentially in the lateral direction.…”
Section: Wall Pressure Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Minnesota studies were based on Dyer's model of the wall pressure correlation function R(r , ,). Tack, Smith and Lambert (1961) measured the properties of this function and found that U. U, the centerline velocity of the tunnel. but that the correlation lengths A. , A 3 and the decay time • were functions of U and of frequency L .…”
Section: Measukements Of Sound Radiated By Bo[ndary-layer-excitmentioning
confidence: 99%